High glucose couples DJ-1 with PTEN to activate PDGFRβ for renal proximal tubular cell injury - Falguni Das; Nandini Ghosh-Choudhury; Balakuntalam S. Kasinath; Kumar Sharma; Goutam Ghosh Choudhury (PLoS ONE, 2025)
High glucose milieu in diabetes induces proximal tubular epithelial cells in the kidney to undergo hypertrophy and matrix protein expansion via Akt/mTORC1 signaling, leading to renal fibrosis. The familial Parkinson’s disease protein DJ-1 acts as a driver of Ras-dependent tumorigenesis and protects dopaminergic neurons from apoptosis. But its function and mechanistic basis to regulate renal fibrosis is not clear. Here, we identify DJ-1 as a high glucose-promoted protein in renal proximal tubular epithelial cells. Mechanistic interrogation revealed that DJ-1 formed complex with the lipid phosphatase PTEN in high glucose-stimulated cells, resulting in phosphorylation/activation of Akt and mTORC1. siRNAs against DJ-1 decreased high glucose-stimulated Akt/mTORC1 activation. In contrast, overexpression of DJ-1 mimicked all effects of high glucose. Interestingly, inhibition of DJ-1 blocked high glucose-induced hypertrophy of proximal tubular epithelial cells and, matrix proteins fibronectin and collagen I (α2) expression while overexpression of DJ-1 mimicked the high glucose effects on these phenomena. Previously, we reported a role of PDGFRβ in proximal tubular cell injury. In exploring the mechanism of DJ-1 function, we found that siDJ-1 inhibited high glucose-induced activating and PI 3 kinase docking site tyrosine phosphorylation of PDGF receptor-β (PDGFRβ) to block phosphorylation of PI 3 kinase. Interestingly, overexpression of PTEN mimicked these effects of siDJ-1. Together, our results reveal an important role of DJ-1-PTEN nodal point for PDGFRβ activation during high glucose-induced proximal tubular epithelial cell injury.